ANALISIS JENIS DAN KADAR SAPONIN EKSTRAK METANOL DAUN KEMANGI (Ocimum basilicum L.) DENGAN MENGGUNAKAN METODE GRAVIMETRI - Mauritz Pandapotan Marpaung; Romelan Romelan (Fakultas MIPA Universitas Tulang Bawang Lampung, 2018)
Kemangi plant (Ocimum basilicum L.) is a plant that has benefits such as overcoming nausea, abdominal bloating, fever, essential oils, vegetable pesticides, fresheners and as a medicine. Kemangi leaves contain phytochemical compounds such as tannins and saponins. The purpose of this research is to analyze the type and content of saponin on kemangi leaf extract by color test and gravimetric method. Samples of kemangi leaves were obtained from Betung area, Banyuasin regency, South Sumatera. Analysis of saponin content, kemangi leaf extract was done by using reflux extraction with methanol solvent. The results showed that the results of the color test, the type of saponin contained from kemangi leaf extract is saponin steroid and the saponin content produced from kemangi leaf extract was 3.11 ± 0.0795%. Keywords: Kemangi leaf, saponin, gravimetry